2017
DOI: 10.4172/2167-7921.1000240
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis and Osteoporosis: A Case Study

Abstract: Metadichol ® is a Nano emulsion of long-chain alcohols called as Policosanol and is present in foods such as rice, sugar cane, wheat, and peanuts. Metadichol ® acts on Nuclear Vitamin D receptors (VDR) that are present in cells throughout the body to stimulate the immune system and inhibit a variety of disease processes, resulting from inflammation to infection [1].We present a case study of a patient with Rheumatoid arthritis with the high levels of RF antibodies, CRP and ESR levels, and low bone mineral dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…have shown that there is an inverse association between vitamin D levels and EPO CKD patients [25]. Vitamin D supplementation and Paricalcitol therapy have been shown to lead to improvement in biomarkers of inflammation [30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…have shown that there is an inverse association between vitamin D levels and EPO CKD patients [25]. Vitamin D supplementation and Paricalcitol therapy have been shown to lead to improvement in biomarkers of inflammation [30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…This paper deals with Metadichol ® expression on UCB cells leading to increased CD33 expression similar to what we saw in CD34 expression. The increased expression observed with CD33 could be one possible mechanism that could explain its diverse pharmacological actions of Metadochol ® on multiple diseases [25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Carynebacterium Diptheraie Diphteriamentioning
confidence: 99%
“…Data analysis 1. Compound activity was analyzed using CBIS data analysis suite (ChemInnovation, CA).…”
Section: Micro Plates Were Read Following Signal Generation With a Pementioning
confidence: 99%
“…Metadichol® is a nano formulation of long chain alcohols that is an inverse agonist of Vitamin D receptor [1]. AHR (Aryl hydrocarbon receptor) like VDR a ligand activated transcription factor.…”
Section: Introductionmentioning
confidence: 99%